Different responses of canopy and shrub leaves to canopy nitrogen and water addition in warm temperate forest - Li, Mengke; Sun, Ruomin; He, Yaqi; Zhou, Tenglong; Mao, Jianing; Li, Wen; Liu, Chang; Ma, Lei; Fu, Shenglei (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the effects of nitrogen deposition and increased rainfall on plants is critical for maintaining forest ecosystem services. Although previous studies primarily examined the effects of environmental changes on leaf functional traits, the underlying physiological and metabolic processes associated with these traits remain poorly understood and warrant further investigation.MethodsTo address this knowledge gap, we evaluated the influence of canopy nitrogen (25 kg ha-1 yr-1) and water (30% of the local precipitation) addition on leaf functional traits, diversity, and associated physiological and metabolic processes in the dominant species of tree and shrub layers.ResultsOnly the interaction between nitrogen and water significantly reduced the functional richness (FRic) of the community. The other treatments had no notable effects on functional diversity. Importantly, the physiological processes of trees and shrubs showed different regulatory strategies. In addition, there were significant changes in 29 metabolic pathways of the tree, whereas only 18 metabolic pathways were significantly altered in shrub. Among the identified metabolic pathways, four were annotated multiple times, with amino acid metabolism being the most active.DiscussionThese regulatory processes enable the leaves to withstand external disturbances and maintain their relative stability under changing environmental conditions. The study findings underscore the limitations of previous research, which often relied on the direct application of treatments to the understory and so failed to accurately assess the effects of nitrogen and water on leaf functional traits. Future studies should adopt canopy-level nitrogen and water addition to better simulate the impacts of global environmental change.